Athlete Perspectives on AI-Driven Coaching Technologies: A Qualitative Inquiry - Ghezelseflou , Hamidreza; Choori, Ali (AI and Tech in Behavioral and Social Sciences, 2023)
This article seeks to understand athletes’ perceptions and experiences with AI-driven coaching technologies. The objective is to identify the major themes associated with the adoption, perceived benefits, challenges, and impact of these technologies on motivation and performance, alongside suggestions for future enhancements. Eighteen athletes across various sports disciplines participated in semi-structured interviews. The study employed a thematic analysis approach to identify key themes and sub-themes related to athletes’ experiences with AI-driven coaching technologies. Ethical approval was obtained from the Institutional Review Board, and informed consent was secured from all participants. Five major themes were identified: Adoption and Adaptation, Perceived Benefits, Challenges and Limitations, Impact on Motivation and Performance, and Suggestions for Improvement. Athletes expressed initial skepticism followed by appreciation for the personalized training and efficiency offered by AI technologies. However, concerns regarding technical issues, lack of personal touch, and data privacy were noted. The impact on motivation and performance was predominantly positive, with athletes acknowledging the role of AI in enhancing training outcomes. Suggestions for improvement emphasized the need for more intuitive user interfaces, enhanced data security, and better integration of human coaching elements. Athletes recognize the transformative potential of AI-driven coaching technologies in enhancing training efficiency, personalization, and injury prevention. Nonetheless, the successful adoption of these technologies hinges on addressing technical challenges, ensuring data privacy, and maintaining the human element in coaching. Future developments in AI-driven coaching technologies should consider athletes’ feedback to refine and tailor these tools, ensuring they meet the unique needs of individuals and foster a productive coach-athlete relationship. Suggestions for future research include expanding the participant pool across a wider range of sports and incorporating longitudinal studies to explore the evolution of athlete perspectives over time.